Alopecia Diffusa while Using Interleukin-17 Inhibitors against Psoriasis Vulgaris - Yajima, Makiko (Case Rep Dermatol, 2019)
We report two cases of alopecia diffusa during the treatment of psoriasis vulgaris with interleukin (IL)-17 inhibitors. Psoriasis is one of the most common immune-mediated chronic skin diseases, strongly associated with IL-17A. Clinically, the monoclonal antibodies to IL-17A or its receptor, IL-17R, show a dramatic effect against psoriasis. Alopecia is also an IL-17-mediated autoimmune disease, and IL-17 inhibitors have been expected to be the gold standard for the treatment of alopecia; therefore, the complication of alopecia while using IL-17 may be regarded as an unexpected “paradoxical reaction.” T helper (Th)17 cells are not cytotoxic enough by themselves to undermine the hair follicle under normal circumstances, they need the coexistence of CD8+ cytotoxic Th1 cells. Th17 cells may be the initiator of the damage of the hair follicle, but CD8 T cells or more powerful Th1 cells are required as followers. The Th17/Th1 axis might convert into a Th1-dominant immune status using IL-17 inhibitors, and the destruction of the hair follicle might result in alopecia. An accumulation of cases is to be expected.